Crime In David Baldacci’s 2013 Novel The Hit: English - Tambolang, Stevan Prima; Maca, Sudirman; Abeng, Andi Tenri (Fakultas Sastra, Universitas Bosowa, 2023)
This study aims to determine the types of crime, causes of crime, and the effects of crime found in the novel The Hit by David Baldacci which was published in 2013 by Grand Central Publishing in USA by analyzing the actions, conversations, and statements made by the main characters in the novel. The research used qualitative descriptive method through forensic approach. The data were obtained by reading, identifying, and taking notes to classify the kinds, causes, and effects of crime in The Hit novel. The writer used sociology of crime theory by Bonger as main theory and forensic text type theory by John Ollson as supporting theory. The result of this study showed that there are 4 types of crime in The Hit novel, such as personal crime, property crime, organized crime, and white-collar crime. The writer also found 3 causes of crime and 3 effects of crime in the novel. The causes of crime in the novel are social cause, economic cause, and psychological cause. While the effects of crime in the novel are material losses, trauma, and loss of life.